EFL Students’ Perceptions on Grammarly Use in Proofreading Essay Tasks - Wahyu, Tri; Zur, Sarjaniah (IAIN KENDARI, 2023)
The mixed method sequential explanatory study aimed to investigate the EFL students’ responses to writing acquisition learning facilitated by Grammarly in terms of lexical process based on their cognitive perspectives in one of the higher Islamic universities in Kendari. The study utilized documentation, questionnaires, and reflection in collecting the data. The data was gathered from 8 participants based on inclusion criteria. The study found that students had responded positively to using Grammarly in proofreading essay tasks. The findings showed that Grammarly had several strengths, such as easiness in using Grammarly, increased student confidence in writing, efficiency in revision, writing improvement, convenience in using Grammarly, writing accuracy, time management, and satisfaction with feedback provided by Grammarly. Meanwhile, Grammarly's weaknesses were consistency and accuracy with the feedback. The study implied that the lecturer or prospective teacher could help improve students' writing in proofreading by using a helpful technology such as Grammarly.Keywords: EFL student’s perceptions; essay tasks; Grammarly; proofreading.